Sejarah Etika Politik dan Hubungannya Dengan Islam - Astriani Astriani; Ahmad Ginannafsih Shafar; Kurniati Kurniati (Ethics and Law Journal: Business and Notary, 2024)
Political ethics in Islam has become a relevant discussion in the context of modern politics. This paper explores the history and practical implications of political ethics in Islam and its relationship to contemporary politics. The history of political ethics in Islam teaches that values ​​such as justice, brotherhood, deliberation and equality are the main foundations in Islamic politics. This research uses qualitative methods to analyze related literature as well as relevant hadiths and verses of the Koran. From this analysis, it was found that political ethics in Islam not only includes the worldly dimension which is related to the relationship between humans and fellow humans and the universe, but also the ukhrawi dimension which is related to the relationship between humans and Allah SWT. The implementation of ethical values ​​in contemporary politics is necessary to maintain integrity, justice and shared prosperity in national and state life. This involves responsible and transparent leadership practices, healthy and inclusive democratic practices, peaceful conflict management, protection of minority rights, and adaptation to the challenges of globalization and information technology. In Indonesia, implementing ethical values ​​in contemporary politics also involves applying the principles of Pancasila and adapting to local conditions and a culture that is rich in diversity. In an effort to build a more ethical and responsible political culture, cooperation between government, political institutions, civil society and the private sector is very necessary. Only with a strong commitment from all parties, can we create a more just, democratic and sustainable political system for a better future. Abstrak Etika politik dalam Islam telah menjadi perbincangan yang relevan dalam konteks politik modern. Jurnal ini mengeksplorasi sejarah dan implikasi praktis dari etika politik dalam Islam serta hubungannya dengan politik kontemporer. Sejarah etika politik dalam Islam mengajarkan bahwa nilai-nilai seperti keadilan, persaudaraan, musyawarah, dan persamaan adalah landasan utama dalam politik Islam. Metode penelitian yang digunakan dalam tulisan ini  adalah metode kualitatif dengan melakukan studi literatur  dari sumber sekunder berupa buku dan jurnal. Dari analisis tersebut, ditemukan bahwa etika politik dalam Islam tidak hanya mencakup dimensi duniawi yang berkaitan dengan hubungan antara manusia dengan sesama manusia dan alam semesta, tetapi juga dimensi ukhrawi yang berkaitan dengan hubungan manusia dengan Allah SWT. Implementasi nilai-nilai etika dalam politik kontemporer diperlukan untuk menjaga integritas, keadilan, dan kesejahteraan bersama dalam kehidupan berbangsa dan bernegara. Hal ini melibatkan praktek kepemimpinan yang bertanggung jawab dan transparan, praktik demokrasi yang sehat dan inklusif, pengelolaan konflik yang damai, perlindungan terhadap hak-hak minoritas, serta penyesuaian terhadap tantangan globalisasi dan teknologi informasi. Di Indonesia, implementasi nilai-nilai etika dalam politik kontemporer juga melibatkan penerapan prinsip Pancasila dan penyesuaian terhadap kondisi lokal dan budaya yang kaya akan keberagaman. Dalam upaya membangun budaya politik yang lebih etis dan bertanggung jawab, kerja sama antara pemerintah, lembaga politik, masyarakat sipil, dan sektor swasta sangat diperlukan. Hanya dengan komitmen yang kuat dari semua pihak, kita dapat menciptakan sistem politik yang lebih adil, demokratis, dan berkelanjutan untuk masa depan yang lebih baik. Kata kunci: Etika politik, Islam, Kontemporer